Does Bleeding During Percutaneous Nephrolithotomy Necessitate keeping the Nephrostomy Tube? A Randomized Controlled Clinical Trial - Etemadian, Masoud; Soleimani, Mohammad Javad; Haghighi, Ramin; Zeighami, Mohammad Reza; Najimi, Neda (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To compare outcomes in two groups of patients with kept and discarded nephrostomy tube after percutaneous nephrolithotomy (PCNL) complicated with bleeding. Materials and Methods: Two hundred patients who had undergone PCNL complicated with hemorrhage were recruited in this study. Patients were randomly allocated to two groups: group A, who underwent tubeless PCNL and tract port was packed for 3 to 4 minutes after removing Amplatz sheath, and group B, for whom a 24-F nephrostomy tube was left in place at the end of the procedure. Patients were followed up for 3 months to check if bleeding occurred. Results: The mean operation time was 68 ± 4.3 minutes in group A and 74 ± 5.6 minutes in group B (P = .098). The mean stone size was similar in groups A and B (36.26 ± 5.3 mm versus 35.35 ± 5.85 mm; P = .613). The mean hemoglobin drop was 3.65 ± 1.20 g/dL in group A and 3.13 ± 1.06 g/dL in group B. There was no significant difference between the mean of stonefree rate in groups A and B (92.58% ± 5.97 versus 89.60% ± 8.3; P = .210). Patients in group A experienced a significantly less duration of hospitalization than group B (2.42 ± 0.84 days versus 3.70 ± 0.80 days; P < .001). Conclusion: In the absence of clear indication, nephrostomy tube insertion after PCNL does not seem to be beneficial, and its removal does not pose patients at any additional risk.